S68 Bioavailability of VEGF in Idiopathic Pulmonary Fibrosis. (19th November 2012) - Barratt, SL; Jarrett, C; Blythe, T; Welsh, GI; Maher, T; Bates, DO; Millar, AB
Abstract : Introduction: Vascular endothelial growth factor (VEGF) is both a growth and permeability factor implicated in the pathogenesis of idiopathic pulmonary fibrosis (IPF). VEGF exerts its biological effects through receptors: VEGFR-1, VEGFR-2, Neuropilin-1(NRP-1) and Neuropilin-2 (NRP-2). The presence of hypoxia and its treatment by high flow oxygen have been proposed to contribute to lung injury. VEGF gene transcription is tightly regulated by a hypoxia response element (HRE). We hypothesised that: VEGF and its receptors would be differentially expressed between normal (NF) and fibrotic fibroblasts (FF). Hypoxia and hyperoxia may alter fibroblast VEGF expression. Methods: NF(n=5) and FF(n=5) (from patients with proven usual interstitial pneumonia) were extracted from lung biopsies using the explant method. VEGF receptors levels were analysed at the mRNA and protein level (qPCR and western blotting (WB)). Pan VEGF isoforms were detected at the protein level using WB and ELISA. Fibroblasts were grown in culture for 24 hours in normoxic, hyperoxic (90% O2) and hypoxic conditions (21% O2 with CoCl2). Results: Both NF and FF expressed VEGFR1, VEGFR2, NRP-1 and NRP-2. No significant difference was detected in receptor expression at mRNA or protein level, but a trend towards reduced protein expression of VEGFR1 and NRP-2 in FF vs NF was observed. FF expressed significantly more total VEGF than NF by ELISA (Figure 1 ): (NF 180.5 pg/ml vs FF 332.0 pg/ml, p=0.01) and by WB (normalised densitometry value: NF 116 vs 162, p=0.046). Moreover, a significant increase in VEGF expression was observed in both normal and fibrotic fibroblasts in response to hypoxic growth conditions (NF 205.7 pg/ml vs 1382.0 pg/ml, p=0.05, FF 394.6 pg/ml vs 1113 pg/ml.0, p=0.01). A trend towards increased VEGF expression was also seen in FFvsNF exposed to hyperoxic conditions. Conclusions: Differential expression of VEGF between NF and FF suggests a potential role in the development of IPF. The observation that hypoxia and possibly hyperoxia may alter VEGF bioavailability has implications in the use of oxygen therapy in the management of this disease.